Toxicological risks in infants and children - Krzystyniak, Krzysztof; Marszałek, Andrzej; Obiedziński, Mieczysław (Health Promotion & Physical Activity, 2016)
Children’s environmental health (environmental pediatrics), based on toxicological, epidemiological and occupational medicine research, has become increasingly visible in the past three decades. Early-life exposure to chemical, nutritional and psychosocial hazards can produce disease and disability in childhood and across the life span. Prevalence of type 1 diabetes (T1D) in children, autistic spectrum disorders (ASD), reproductive system disorders, allergy and other chronic diseases in children increased dramatically in several recent decades. Their etiology and epidemiology in populations of Western Countries remain unsolved. Many scientists agree that the interactions of environmental factors with gene susceptibilities have been relatively overlooked in these diseases.